2023
DOI: 10.1021/jacs.2c09359
|View full text |Cite
|
Sign up to set email alerts
|

Programming DNA Circuits for Controlled Immunostimulation through CpG Oligodeoxynucleotide Delivery

Abstract: Herein, we present a DNA circuit programmed for the delivery of CpG oligodeoxynucleotides (CpG ODNs) with the pharmacological immunostimulation function. The circuit employs a complementary DNA (cDNA) strand to deactivate the biological function of CpG ODNs via hybridization, while T7 exonuclease mediates the activation by hydrolyzing the cDNA and releasing the CpG ODN as an active moiety. We investigated the influence of several factors on the kinetic profile and temporal behavior of the circuit. These includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…Particularly, the biocompatibility of the DNA tetrahedral circuit and its versatile applicability are noteworthy. Beyond demonstrating the unprecedented use of programmed entropy-driven circuits stimulating biological responses in cells and contribution of the principles to the development of biosensors, biomedicine, and Systems Chemistry, broader impacts of the concepts may be envisaged: (i) The triggered release of other functional nucleic acids by the entropy-driven circuit, such as ribozymes, antisense oligonucleotides, or splicing DNAzymes as control units of gene/protein expression pathways, may be designed. , Also, aptamers could be linked to the reaction module and activate the circuit by aptamer/ligand complexes . (ii) The study demonstrated the primer-induced entropy-driven cascaded emergence of two CDNs.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the biocompatibility of the DNA tetrahedral circuit and its versatile applicability are noteworthy. Beyond demonstrating the unprecedented use of programmed entropy-driven circuits stimulating biological responses in cells and contribution of the principles to the development of biosensors, biomedicine, and Systems Chemistry, broader impacts of the concepts may be envisaged: (i) The triggered release of other functional nucleic acids by the entropy-driven circuit, such as ribozymes, antisense oligonucleotides, or splicing DNAzymes as control units of gene/protein expression pathways, may be designed. , Also, aptamers could be linked to the reaction module and activate the circuit by aptamer/ligand complexes . (ii) The study demonstrated the primer-induced entropy-driven cascaded emergence of two CDNs.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Governed by the Watson–Crick base paring rules, DNAs with unique programmability and affordability have become unparalleled scaffolds for engineering nanodevices and molecular machines. 3,4 In particular, owing to the easy-to-predict thermodynamics and good biocompatibility, such DNA-based nanostructures have exhibited excellent performance when interacting with biological elements, which show great promise in biosensing and bioimaging, 5,6 specific cargo delivery, 7,8 molecule computation, 9–11 and so on. Despite the progress made, the majority of current DNA nanodevices still operate in an “always on” model.…”
Section: Introductionmentioning
confidence: 99%
“…16 In particular, the endogenous stimuli-controlled strategies ( e.g. pH, 17 small molecules, 18 enzymes, 19,20 etc. ) have become prominent tools for regulating the specific imaging ability of DNA nanodevices, in which the use of endogenous substances can maintain the native state of live entities and avoid organ injuries.…”
Section: Introductionmentioning
confidence: 99%